Does Oxidative Stress Impact Bovine Reproductive Disorders? - Katiyar, R.; Deori, S.; Singh, M. (The Indian Journal of Animal Reproduction, 2021)
Oxidative stress indicates an imbalance between pro-oxidants and antioxidants mechanisms of the body. The elevated production of stress level affects physiological functions of female reproduction. Literatures pertaining to oxidative stress have become an active area of research investigation now a day in livestock species particularly in veterinary medicine in general and reproduction in particular. This is because of the increased incidence of infertility problems in livestock and perhaps will remain as emerging area of research in the coming decades. The oxidative stress is surmised to have role in pathophysiology of female infertility. From a clinical perspective, it is of utmost importance to have knowledge in respect to impact of oxidative stress in bovine infertility. This review focuses on the pathogenesis of various bovine reproductive disorders such as cystic condition, endometritis, retained fetal membrane, embryonic mortality and repeat breeding with respect to oxidative stress.